Critical Discourse Analysis in the “What a Wonderful World” Song Lyrics by Louis Armstrong - Nihta V. F. Liando; Sanerita T. Olii; Fivy Andries (English Education Postgraduate Program, Universitas Negeri Manado, 2022)
This research wants analyse a popular song around the world entitled “What a Wonderful World”. The song has become popular in every generation. This research follows Fairclough’s three inter-related processes of analysis tied to three inter-related dimensions of discourse as follow: (1) The object of analysis (2) The processes by means of which the object is produced and received by human as subjects. (3) The socio-historical conditions which govern these processes. The song lyric become the object of this research. Critical Discourse Analysis (CDA) used in analyse the song lyric by connecting to the social context in Indonesia. The result shows (1) Armstrong describes world as wonderful, although the singer himself is a black American that faced prejudice and bitterness (2) The song was written during hard time, a terrible turmoil in American society. (3) The song had released on 1967, on that time, the daily life and politic situation of America are disturbed. It is full of hatred and prejudice of racialism. The lyrics in the song offers description of how the world could be wonderful if we wonders and appreciate nature and create a good friendship, indirectly this song brings hope for the better future. Relate to the social context in Indonesia, this song lyric become as a good reminder for Indonesian to keep the wonderful, peaceful, and harmonization atmosphere, remembering Indonesia has many diverse culture, religion, racial, and ethnic. This research expected to remind people in every field not only in ELT, the power of love in giving hope for the future and to make world become better by what we are doing to the world with love nature and create a good relationship with anyone.